Evaluation of the Physical Quality of Supplement Wafer and Application of Supplement on Layer Performance - Anna Megawati Br Pakpahan; Yuli Retnani; Rita Mutia; Wira Wisnu Wardani (Buletin Peternakan, 2023)
This study aimed to evaluate the physical quality of the wafer supplement with different binders and evaluate the performance of laying hens fed the supplement wafer in drinking water. The rearing stage used 64 Isa Brown chickens raised for 12 weeks. Stage 1 of the experiment used a 3x4 Completely randomized design (T1: Pollard, T2: Cassava Flour, T3: Tapioca Flour Waste). Phase two of the study used a completely randomized design with two treatments x 4 replicates x 8 chickens (P0: without supplement wafers, P1: supplement wafers). The variables observed were the wafer's physical quality and Isa Brown's performance. Different adhesives in the manufacture of wafers produced no significant difference in water content (p>0.05) but significant differences (p<0.05) in water activity, bulk density, wafer durability index, and total solubility. Supplementary wafer administration did not affect (p>0.05) feed consumption, drinking water consumption, Feed Conversion Ratio (FCR), egg weight, and daily egg production but did affect (p<0.05) chicken mortality. The conclusion is that wafers with the best physical quality use cassava flour binder, and giving wafer supplements in drinking water can reduce mortality.